(untitled) (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2019)
This work, besides making a careful examination, represents a real journey inside of a world that has gone through times and places, broke patterns of the past to live without, has undergone changes and revolutions, has known love to destroy hatred, is the knowledge of the movement, the movement of the body and mind ... is the hip hop!! The word "hip hop" contains the term "movement", that it is not only part of its meaning, but is what it represents. The hip hop, in fact, is born and begins to move from a road, or rather from a more restricted and circumscribed place, a house in the neighborhood between you forgotten and abandoned, the Bronx, to spread and take over the entire world. The importance of this phenomenon resides in the factor, that in the early 70s its creators and founders were all teenagers. The world of hip hop, which now affects and imposes itself in the world of fashion, music, language and society, was founded by young people. The hip hop was born from young adolescents of New York and took the world by storm. Over the years he has found a way to break down the barriers that surrounded him, being able to fit into so universal culture and to influence it and change it profoundly. It changed the way we live and stand in the street: from clashes and territories conquests, to a no more shots of gunfire, but sound of scratch and spray. It moved the people making them move and do not die. It moved crew and no gang. It moved minds to create and invent steps, rhymes and lines. It moved fashions, cultures and thoughts uniting and not dividing them. This journey from the gang to the crew begins by providing the reading and analysis keys with which is possible understand and thoroughly investigate birth, origin, causes and evolution of the gang going from New York suburbs up to the main Italian cities. The route continues by examining how many of these gangs have abandoned the path of violence undertaking a new way of re-socialization through the hip hop culture and how this phenomenon is rooted in the world. Through calligraphic analysis, interviews with writers, life stories of street people and contributions on DJing and legality, the journey ends interpreting and expressing the thoughts on the studies and on the investigations examined.